Preparation of plasticized wheat gluten/olive pomace powder biocomposite: Effect of powder content and chemical modifications - Remini, Hocine (university bouira, 2015)
During the last decades, a lot of interest was given to the biocomposites development, due to the low cost and degradability of waste food industries. In this study, biocomposites were developed from Wheat Gluten plasticized by 35% of glycerol, containing 0–20% of Clean Olive Pomace (COP), Esterified Clean Olive Pomace (ECOP), or Mercerized Clean Olive Pomace (MCOP) powders, which were prepared by conventional blending. Chemical modifications of the powders were characterized by Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), and thermogravimetric analysis (TGA). Mechanical properties, water absorption, mass loss and thermal properties of biocomposites were detailed. It was found that thermal stability of powder was improved after mercerization. Incorporation of COP powder (20%) in plasticized wheat gluten (WG) improved significantly Young's modulus …